Literature Review : Potential of Bamboo Leaves (Bambusa Sp.) as Antioxidants for Health, Especially Diabetes - Erlina Nur Arifani; Andita Eltivitasari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Diabetes mellitus, especially type 2, is a growing epidemic with almost 90% of cases reported worldwide. Antioxidants are compounds that are in lower concentrations compared to the concentration of oxidizable compounds, can significantly prevent or inhibit the oxidation of the substrate. The formation of more stable oxidant compounds through intramolecular hydrogen bonds in the further oxidation process. Data collection was carried out using Google Scholar, Science Direct and PubMed databases. The literature sources used were in the form of research results that had been published in 2011-2021 in national and international journals. Providing antioxidants is an effort to inhibit the production of intracellular free radicals or increase the ability of defense enzymes against free radicals in order to prevent the emergence of oxidative stress and diabetes-related blood vessel complications. Various supplements containing antioxidants and/or factors that can increase the production of nitric oxide (NO) have the potential to improve endothelial dysfunction and mitochondrial function in cells, as well as reduce the activity of the NAD(P)H oxidase enzyme.